Communication Tools for the Enhancement of Effective Management and Governance at Institutions of Higher Learning: A Case of the University of Venda - Dzaga, T. V. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
The study investigated the contribution of communication tools for the enhancement of effective management and governance at institutions of higher learning with particular focus on the University of Venda. The study was premised on the fact that identification and availability of communication tools influence the effective management and governance at institutions of higher learning. A total of 523 people – staff, students, alumni and council members were sampled in this mixed method study. Hence, data were analysed both quantitatively and qualitatively. The study revealed that stakeholders are rarely consulted in decision-making processes, for them to support the policies. The study also revealed that when stakeholders are poorly informed they may lose confidence in the institution, particularly the executive leadership. The study further revealed that poor bottom-up communication can result in employees failing to understand the expectations of the institutional leadership which could eventually lead to a communication vacuum. It is envisaged that the study will inform policy formulation and implementation processes within the communication space at institutions of higher learning as improved communication would enhance relationship between institutions and their stakeholders.
Journal article published in the International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Communication tools; Governance; Institutions of higher learning; Management; Public administration; Communication in higher education